Transforming healthcare through regenerative medicine. Issue 1 (December 2016) - Jessop, Zita; Al-Sabah, Ayesha; Francis, Wendy; Whitaker, Iain
Abstract Regenerative medicine therapies, underpinned by the core principles of rejuvenation, regeneration and replacement, are shifting the paradigm in healthcare from symptomatic treatment in the 20th century to curative treatment in the 21st century. By addressing the reasons behind the rapid expansion of regenerative medicine research and presenting an overview of current clinical trials, we explore the potential of regenerative medicine to reshape modern healthcare.